A Virome and Proteomic Analysis of Placental Microbiota in Pregnancies with and without Fetal Growth Restriction - Aleksandra Stupak; Maciej Kwiatek; Tomasz Gęca; Anna Kwaśniewska; Radosław Mlak; Robert Nawrot; Anna Goździcka-Józefiak; Wojciech Kwaśniewski (Cells)
Introduction: Metagenomic research has allowed the identification of numerous viruses present in the human body. Viruses may significantly increase the likelihood of developing intrauterine fetal growth restriction (FGR). The goal of this study was to examine and compare the virome of normal and FGR placentas using proteomic techniques. Methods: The study group of 18 women with late FGR was compared with 18 control patients with physiological pregnancy and eutrophic fetus. Proteins from the collected afterbirth placentas were isolated and examined using liquid chromatography linked to a mass spectrometer. Results: In this study, a group of 107 viral proteins were detected compared to 346 in the controls. In total, 41 proteins were common in both groups. In total, 64 proteins occurred only in the study group and indicated the presence of bacterial phages: E. coli, Bacillus, Mediterranenean, Edwardsiella, Propionibacterium, Salmonella, Paenibaciilus and amoebae Mimiviridae, Acanthamoeba polyphaga, Mimivivirus, Pandoravirdae, Miroviridae, Pepper plant virus golden mosaic virus, pol proteins of HIV-1 virus, and proteins of Pandoravirdae, Microviridae, and heat shock proteins of the virus Faustoviridae. Out of 297 proteins found only in the control group, only 2 viral proteins occurred statistically significantly more frequently: 1/hypothetical protein [uncultured Mediterranean phage uvMED] and VP4 [Gokushovirus WZ-2015a]. Discussion: The detection of certain viral proteins exclusively in the control group suggests that they may play a protective role. Likewise, the proteins identified only in the study group could indicate a potentially pathogenic function. A virome study may be used to identify an early infection, evaluate its progress, and possible association with fetal growth restriction. Utilizing this technology, an individualized patient therapy is forthcoming, e.g., vaccines.